Implication of eating behavior and some life habits in the academic stress of Moroccan university students - Kourisna, Abla; Arfaoui, Amine; Zghaid, Mustapha; Aboussaleh, Youssef (Progress in Nutrition, 2026)
Abstract.Introduction: The objective of this study is to investigate the relationship between academic stress, eating behavior, and life habits among Moroccan university students. Methods: A cross-sectional survey was conducted among students enrolled in Bachelor's degree programs at Ibn Tofail University. Data were collected through a questionnaire distributed both online and in paper form. The questionnaire included sections on dietary habits, lifestyle behaviors, and academic stress levels. A total of 200 students participated in the study. Statistical analysis was performed using SPSS software, and significance was determined at p < 0.05. Results: The results showed that 62% of students experienced moderate to high levels of academic stress, with female students reporting higher stress levels than males. It was found that students who consumed fewer than three meals per day and those who frequently snacked had significantly higher stress levels. Awareness of the nutritional value of foods was also associated with higher stress levels. No significant relationships were found between academic stress and factors such as residence, body mass index, sleep duration, physical activity, health problems, smoking, or alcohol consumption. Conclusion: This study highlights the strong association between academic stress and unhealthy eating behaviors among university students. These findings suggest the need for support and educational programs to help students manage stress and adopt healthier eating habits, ultimately contributing to their overall well-being and academic success.